Comparative immune response during the juvenile and adult stages of two abalones under Vibrio harveyi challenge. Issue 98 (March 2020) - Shen, Yawei; He, Tingting; Luo, Xuan; Ke, Caihuan; You, Weiwei
Abstract: Mass mortality of juvenile hybrid ( Haliotis discus hannai ♀× H. fulgens ♂, DF) and adult H. discus hannai (DD) occurs in south China during the summer. This study showed that the juvenile DF and adult DD exhibited significantly lower survival rates than juvenile DD and adult DF under 72 h pathogenic bacteria ( Vibrio harveyi ) challenge at different temperatures (20 °C and 28 °C). Phenoloxidase (PO) and superoxide dismutase (SOD) activities were significantly higher in juvenile DD compared to juvenile DF, whereas that in adult abalone was the opposite. Juvenile DD and adult DF also exhibited advantages in terms of immune-related gene expression ( TRAF, TLR, MIF, Lys, Spi, Cat, TNF, and SOD ) compared to juvenile DF and adult DD. The data reveals immunocompetence differences in DD and DF at the juvenile and adult stages. Highlights: Juvenile hybrid (DF) and adult Pacific abalone (DD) were weaker than juvenile DD and adult DF under bacteria challenge. PO and SOD activities were significantly higher in juvenile DD and adult DF. Juvenile DD and adult DF exhibited advantages in terms of immune-related genes' expression.